Crowd Evacuation through Crossing Configurations: Effect of Crossing Angles and Walking Speeds on Speed Variation and Evacuation Time - SayedMohammed, Shabna; Verma, Anshi; Dias, Charitha; Alhajyaseen, Wael; Almukdad, Abdulkarim; Aghabayk, Kayvan (Sustainability, 2022)
The design of safe and efficient pedestrian facilities necessitates the knowledge of complex human movements, such as intersecting pedestrian streams, under different conditions. This study aims to experimentally investigate the impact of intersecting angles on collective crowd dynamics under two different urgency levels. Data were collected from a controlled laboratory experiment with scenarios consisting of three intersection angles (30°, 90°, and 150°) and two desired speed levels (normal walking and slow running). Trajectory data of individual experiment participants were extracted from the recorded video footage. The results indicate that the 30° intersection has the lowest bottleneck effect compared to the other angles. Moreover, the time-to-target analysis shows that the 150° intersection has a higher waiting time at the intersection compared to the other angles for the jogging scenarios. The speed distribution and space utilization maps implied an asymmetrical reduction in speed in the two corridors of the intersection, even though the physical and geometrical configurations are symmetric. The lane-based analysis of collective speeds revealed that the inner lane (the lane that initially encounters the intersecting flow) has the maximum reduction in speed. The outcomes of this study may be useful to evaluate the congestion effects associated with crossing configurations and in calibrating and validating simulation tools to reproduce such effects accurately.